Precoding algorithm based on IQ imbalance in massive MIMO - Jun WANG; Jianxin DAI; Chonghu CHENG; Peng WANG; Sha LI (Dianxin kexue)
Massive multiple-input multiple-output（MIMO）refers to the idea equipping cellular base stations with a very large number of antennas，and is a communication way of severing several users. Widely-linear optimized block diagonalization type precoding techniques was proposed to alleviate the impact of IQ imbalance in the downlink massive multi-input multi-output systems. Numerical results show that significant performance can be gain compared to BD and WL-BD.